2023
DOI: 10.1093/plphys/kiad407
|View full text |Cite
|
Sign up to set email alerts
|

A cell wall–localized β-1,3-glucanase promotes fiber cell elongation and secondary cell wall deposition

Abstract: β-1,3-glucanase functions in plant physiological and developmental processes. However, how β-1,3-glucanase participates in cell wall development remains largely unknown. Here, we answered this question by examining the role of GhGLU18, a β-1,3-glucanase, in cotton (Gossypium hirsutum) fibers, in which the content of β-1,3-glucan changes dynamically from 10% of the cell wall mass at the onset of secondary wall deposition to < 1% at maturation. GhGLU18 was specifically expressed in cotton fiber with highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…We found that the fiber length of xin w 139 was also reduced by approximately 40% compared to that of Xin W 139, indicating that fiber elongation was not completed at 20 DPA. At 20 DPA, the transition from the fiber elongation stage to the fiber secondary wall synthesis stage occurs [ 28 ]. At 20 DPA, the SCW begins to be deposited on the inner side of the primary wall so that the elongation of the fibroblasts and the thickening of the SCW overlap for a period [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the fiber length of xin w 139 was also reduced by approximately 40% compared to that of Xin W 139, indicating that fiber elongation was not completed at 20 DPA. At 20 DPA, the transition from the fiber elongation stage to the fiber secondary wall synthesis stage occurs [ 28 ]. At 20 DPA, the SCW begins to be deposited on the inner side of the primary wall so that the elongation of the fibroblasts and the thickening of the SCW overlap for a period [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result was also supported by the increased hemicellulose contents of OE-MUR3 fibers (Figure S3b). Previo us studies reported that the overexpression of GhGLU18 and GhGalt1 also significantly increased the expression of genes involved in cell wall synthesis and influenced fiber length and cell wall thickness (Fang et al, 2023;Qin et al, 2017). Xylan and lignin can directly activate the expression of glycosyltransferases associated with seco ndary wall synthesis (McCarthy et al, 2010).…”
Section: Ghmur3 Plays An Important Role In Cotton Developmentmentioning
confidence: 99%
“…Overexpression of GhGalT1 (b-1,3-Galacto syltransferase) affects monosaccharide components of fiber and reduces fiber length (Qin et al, 2017). GhGLU18 is a b-1,3-glucanase that is highly expressed in the seco ndary wall thickening stage, and the fiber length of overexpression lines is significantly increased (Fang et al, 2023). MUR3 belongs to glycosyl transferase subfamily 47 (GT47), which is one of the key enzymes in the synthesis of xylo glucan side chains and plays an important role in maintaining cell morphology and cell elongation (Kong et al, 2015;Tamura et al, 2005).…”
Section: Ghmur3 Plays An Important Role In Cotton Developmentmentioning
confidence: 99%
“…Events such as CFML degradation, accumulation of callose, and SCW cellulose leads to fiber CW rigidification and increased strength (Maltby et al 1979;Jaquet et al 1982;Rowland et al 1984;Martel and Giovannoni 2007;Vicente et al 2007;Pettolino et al 2022;Fang et al 2023).…”
Section: Predicted Polysaccharide Epitopes and Cw Synthesizing Enzyme...mentioning
confidence: 99%